Impedance analysis and modeling of a gold microelectrode array (MEA) using black platinum - Velarte, Antonio; Otín Acín, Aránzazu; Pueyo Paules, Esther (Jornada de Jóvenes Investigadores del I3A, 2022)
This work evaluates the suitability and performance of a microelectrode array (MEA) by measuring and modifying its impedance. For this purpose, the electrical model that best fits the impedance curve obtained has been analyzed and proposed, and a noise analysis has also been performed.